A novel compound heterozygous variant in SMARCAL1 leading to mild Schimke immune-osseous dysplasia identified using whole-exome sequencing. Issue 4 (April 2021) - Wang, Li; Li, Jingjing; Wu, Ge; Kong, Xiangdong
Schimke immuno-osseous dysplasia (SIOD) is a rare autosomal recessive inherited disorder that is caused by the SMARCAL1 mutation. The phenotype can vary from mild to severe on the basis of the patient's age at onset. Herein, we report the case of a 14-year-old Chinese boy who presented with short stature, focal segmental glomerulosclerosis (FSGS), and facial dysmorphism. Genetic analysis revealed two compound heterozygous missense mutations, including a well-known mutation (c.1933C>T, p.R645C) and a novel mutation (c.2479G>A, p.V827M) in the SMARCAL1 gene, which were inherited from his parents. In silico analyses showed that the c.2479G>A (p.V827M) variant affects a highly conserved residue within the ATPase catalytic domain. Finally, we established the diagnosis of mild SIOD and treated the patient with diuretics and angiotensin receptor blockers. This report expands the mutational spectrum of SMARCAL1 and reinforces the importance of a detailed clinical evaluation, molecular detection, and appropriate genetic counseling.